Analisis Karakteristik Ibu, Pengetahuan dan Kebiasaan Merokok dengan Kejadian ISPA pada Balita di Kelurahan Kenali Asam Bawah - Tina Yuli Fatmawati (Universitas Batanghari Jambi, 2018)
Word Health Organization (WHO) estimates the incidence of Acute Respiratory Infections (ISPA) in the World with infant mortality rates above 40 per 1000 live births and 15% -20% per annum in under-five age groups. In Jambi, ISPA is the most common disease of the 10 major diseases. The purpose of this study was to determine whether there was a relationship between maternal characteristics, knowledge and smoking habits with the incidence of ISPA in infants in the Posyandu Kelurahan Kenal Asam Bawah. This reseach is a description corelation with a cross sectional design, carried out in December 2017. The sample were mothers who had toddlers aged 1-5 years who were in 2 Posyandu in Kenali Asam Bawah, with a sample of 90 respondents with Total sampling technique. Data analysis used was univariate analysis and bivariate analysis with Chi-Square test. The results showed that from 90 respondents most of the education of highly educated respondents were 61 (67.8%), most of the age of toddlers at 1-3 years old were 57 (63.3%), the majority of respondents had low knowledge of 48 mothers (53.3%), Most of them were family smokers, 62 respondents (58.9%), there was a relationship between maternal education, knowledge and smoking habits with the incidence of ISPA in infants in Posyandu Kelurahan Kenali Asam Bawah with p-value 0.023, 0.004 and 0.000 (p <0, 05). It is recommended that Puskesmas can increase activities in planning disease control programs, especially ISPA.